2006
DOI: 10.1111/j.1469-7580.2006.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination secondary to chronic nerve compression injury alters Schmidt–Lanterman incisures

Abstract: The role of Schmidt-Lanterman incisures (SLIs) within the myelin sheath remains the subject of much debate. Previous studies have shown a positive correlation between the number of SLIs per internode and internodal width for both normal and pathological myelin internodes. As chronic nerve compression (CNC) injury induces demyelination, we sought to evaluate if CNC injury altered the occurrence of SLIs using nerve-teasing techniques and light microscopy. Rigorous examination of the teased axons from nerves subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…17 Our previously published research has consistently demonstrated that the dimensions of the tube are sufficient to cause compression without causing deformity to the nerve and thereby, inducing a progressive decrease in nerve conduction velocity. 16,17,[26][27][28][29][30][31][32][33] With the development of this rat model for CNC, we had found that tubing that constrained the nerve caused scarring at the site and subsequent axonal loss which is a different pathology from conditions seen in humans such as carpal tunnel syndrome. The tubing with its current dimensions comes into contact with the nerve and is able to transmit sufficient pressure to cause the subsequent changes we have observed in repeated studies at the cellular level.…”
Section: Discussionmentioning
confidence: 96%
“…17 Our previously published research has consistently demonstrated that the dimensions of the tube are sufficient to cause compression without causing deformity to the nerve and thereby, inducing a progressive decrease in nerve conduction velocity. 16,17,[26][27][28][29][30][31][32][33] With the development of this rat model for CNC, we had found that tubing that constrained the nerve caused scarring at the site and subsequent axonal loss which is a different pathology from conditions seen in humans such as carpal tunnel syndrome. The tubing with its current dimensions comes into contact with the nerve and is able to transmit sufficient pressure to cause the subsequent changes we have observed in repeated studies at the cellular level.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the altered appearance, i.e. increased prominence of pre-existing incisures during Wallerian degeneration (Krinke et al, 1986) and the increased occurrence of SLCs in nerves consisting of new myelin after chronic nerve compression (Berger and Gupta, 2006) suggest a role of SLCs during degeneration and also in maintenance of the myelin sheath.…”
Section: Introductionmentioning
confidence: 98%
“…Under different pathological conditions, the appearance of SLIs can be altered, suggesting that these structures might play a role in myelin maintenance [Berger and Gupta, 2006]. In human inherited peripheral neuropathies (i.e., Charcot-Marie-Tooth type 1A disease), the organization of myelinated nerve fibers is altered.…”
Section: Introductionmentioning
confidence: 99%